The Influence of Social Responsibility and Leverage on Company Value with Profitability as Mediator - Yunita Kurniawat; Suwardi B. Hermanto; Bambang Suryono (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to analyze the effect of social responsibility (CSR) and Leverage on firm value with profitability as a mediating variable in mining companies listed on the BEI for the period 2014-2019. The sample in this study was selected using purposive sampling technique, with the number of samples obtained as many as 13 companies and a total sample of 78 companies for 6 years. This study uses multiple linear regression analysis to test the direct effect and technical analysis of simple mediation (simple mediation) with the causal step. The results of this study indicate that: 1) CSR disclosure has an effect on profitability. 2) Leverage affects profitability. 3) CSR disclosure has no effect on firm value. 4) Leverage has a negative effect on firm value. 5) Profitability has a negative effect on firm value. 6) Profitability is able to mediate the influence of social responsibility on company value. 7) Profitability is able to mediate the effect of Leverage on firm value.